Chemokine receptors in Atlantic salmon. Issue 1 (March 2015) - Grimholt, Unni; Hauge, Helena; Hauge, Anna Germundsson; Leong, Jong; Koop, Ben F.
Highlights We found 48 chemokine receptors in Atlantic salmon. 40 of these receptors had expressed support. 18 receptors are duplicated mainly due to the unique salmonid whole genome duplication. The main variation between duplicates reside in ligand binding and signalling domains.